PENGARUH PENILAIAN PRESTASI KERJA DAN PELATIHAN KARYAWAN TERHADAP PROMOSI JABATAN PADA PT BANK MANDIRI KCP ARIVAI PALEMBANG - Maswah .; Yunidar Erlina; Sondang Rouli Silitonga (JURNAL KOMPETITIF, 2019)
The purpose of this study was to determine and analyze the effect of performance appraisal and employee training on job promotions at PT Bank Mandiri KCP A.Rivai Palembang. This research is a type of causal associative research that aims to analyze the relationship between one variable with another variable or how a variable affects other variables. The population in this study were all employees with a minimum service life of 5 years. The sampling method using the census method with a total sample of 36 people. Primary data is collected through questionnaires and interviews, secondary data is collected from companies and literature studies. Data analysis method used is descriptive and quantitative analysis methods with multiple linear regression analysis techniques. The results showed that the variable performance appraisal and employee training simultaneously or partially had a positive and significant effect on the promotion of the position of PT Bank Mandiri KCP A.Rivai Palembang with the contribution of Adjusted R Square of 51.5% promotion was influenced by the variable performance appraisal and training employee, the multiple regression equation is obtained: Y= 8,517 + 0,584 (x1) +  0,277 (x2)  + e   while the remaining 48.5% is influenced by other factors not included in this study. Keywords: Job Performance Evaluation, Employee Training, and Job Promotion